“Byzantine Myth” in the Historiography of Pre-Mongol Rus’ - Valerii Pavlovich Stepanenko (Античная древность и средние века)
This article analyses the scholarly works of historians and art historians written from the mid-twentieth to the early-twenty-first century, discussing the Rus’ian-Byzantine contacts from the eleventh to thirteenth century. The author of this article highlights that addressing Byzantine history allows the researchers to interpret Rus’ as a state with the culture developing in parallel with the Byzantine, being in no way inferior to it. However, some of the researchers’ ideas are based on erroneous interpretations of chronicle’s accounts or are purely hypothetical, as they do not find any support in archaeological or written sources. Moreover, sometimes the researchers show a lack of knowledge on the history of Byzantium. This article also discusses the most common historiographical errors. Finally, it has been noted that in the works published of recent decades supply not always successful attempts to reconstruct the cultural contacts of Rus’ (primarily, of the cities of Vladimir and Novgorod) with Byzantium and Western Europe under Vsevolod the Great Nest, as well as under the Byzantine Emperor Manuel I Komnenos.